1968
DOI: 10.1037/h0025818
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of adrenaline and noradrenaline during prolonged immobilization.

Abstract: SS WHO SUCCESSFULLY COMPLETED 1 WK. OF IMMOBILIZATION SHOWED NO SIGNIFICANT CHANGES IN SUBJECTIVE STRESS AND MOOD OR IN THE URINARY EXCRETION OF ADRENALINE AND NORADRENALINE (CATECHOLAMINES) RELATIVE TO RECUMBENT CONTROLS. THE CATECHOLAMINE EXCRETION OF THE IMMOBILIZATION QUITTERS WAS RELATED TO THEIR ENDURANCE. EARLY QUITTERS SHOWED NO SIGNIFICANT CHANGES; LATE QUITTERS SHOWED AN INCREASE, PARTICULARLY IN ADRENALINE EXCRETION. ANOTHER CHARACTERISTIC OF THE QUITTERS WAS THE PRESENCE OF A LOWER BASE-LINE LEVEL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1968
1968
1996
1996

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The results of the 12 successful, perceptually deprived immobilized Ss (IPD group), on the biochemical and affective measures, were compared with the results of 16 immobilized (I group) and 16 recumbent control 5s (RC group) from a recent study (Zubek, 1968) employing the same cofflnlike box, 1-wk. duration, and measures as the IPD group but using Ss exposed to normal visual and auditory stimulation.…”
Section: Comparison Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the 12 successful, perceptually deprived immobilized Ss (IPD group), on the biochemical and affective measures, were compared with the results of 16 immobilized (I group) and 16 recumbent control 5s (RC group) from a recent study (Zubek, 1968) employing the same cofflnlike box, 1-wk. duration, and measures as the IPD group but using Ss exposed to normal visual and auditory stimulation.…”
Section: Comparison Groupsmentioning
confidence: 99%
“…In a series of experiments from the Manitoba laboratory (Zubek, 1968;Zubek & Mac-Neill, 1966;Zubek & Wilgosh, 1963), it has been shown that Ss whose level of kinestheticproprioceptive stimulation was reduced by immobilization but who otherwise were exposed to a normal and varied sensory environment for a week exhibited a variety of cognitive and perceptual-motor deficits, unusual subjective phenomena, a slowing of the electrical activity of the brain, a reduced urinary excretion of catecholamines (adrenaline and noradrenaline), and no changes in subjective stress and mood. However, a comparison of the results of the immobilized 5s with those of control 5s revealed that most of the effects were associated with either the recumbent position or with a combination of recumbency and restricted motor activity.…”
mentioning
confidence: 99%
“…One of the more striking findings is the tendency for some of the volunteer 5s to find the stress situation intolerable and to quit the experiment. Zubek (1968) recently reported that the "quitters" in his study excreted initially less urinary catecholamines than 5s who were able to tolerate the procedure for longer durations. This is of interest since a deficiency in epinephrine and norepinephrine is known to exist in PKU (Nadler & Hsia, 1961).…”
Section: Conclusion and Discussionmentioning
confidence: 94%
“…Fiske and Maddi (1961) have emphasized two features bearing on the severity of aftereffects: the degree of physical immobilization and the number of sense modalities affected. Zubek (1963aZubek ( , 1963bZubek ( , 1964aZubek ( , 1964bZubek ( , 1964cZubek ( , 1968) has elucidated the nature of immobilization by itself and in conjunction with other means of sensory restriction in adult volunteers. One of the more striking findings is the tendency for some of the volunteer 5s to find the stress situation intolerable and to quit the experiment.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Among volunteers who quit the experiment, those who quit somewhat later in the deprivation period are very much more distressed than nonquitters or than people who quit very early (Zubek, 1968). These different levels of disturbances show up on a variety of measures including steroid outputs.…”
Section: The Response To Subjective Experiencementioning
confidence: 99%